Kate Gordon’s pragmatist aesthetics: A historiographical recovery - Haubert, Laura-Elizia (Estudios de Filosofía, 2025)
Although Kate Gordon is today an almost unknown figure in philosophical historiography, she can be considered one of the pioneers of pragmatist aesthetics. The research hypothesis developed here is that Gordon’s aesthetic work, produced in the first decade of the twentieth century, should be recovered from oblivion, as she was the first philosopher, on the one hand, to openly declare that her aesthetic theory adopted a pragmatist perspective and, on the other, to question what it would mean to transpose the pragmatist method to the field of aesthetics and the philosophy of art. This study employed a bibliographical method to review the most relevant articles by the author. It concludes that Gordon’s aesthetics — both in terms of its topics of interest and the concepts it develops — anticipates by decades the better-known contributions to pragmatist aesthetics, such as those later formulated by John Dewey. Therefore, she should be recognized as one of the notable forerunners of this tradition.